Mapping brazilian dentistry research trends: A bibliometric analyzes - Sigolo, Brianda de Oliveira Ordonho [UNESP]; Calabrez, Ana Paula Aparecida; Almeida, Catia Candida de; Casarin, Helen de Castro Silva [UNESP] (Univ Federal Parana, Dept Ciencia & Gestao Informacao, 2024)
Introduction: Through the scientific mapping of keywords by dentistry authors affiliated with Brazilian institutions, we identified the trends and evolution of the research themes in the field using data collected from scientific publications in the area indexed in the Web of Science and Scopus databases between 2012 and 2021. Method: We analyzed the 20 most used keywords and extracted the co-occurrence networks and strategic diagrams from them. Results: The results showed continuous growth in the use of the terms dental implants, oral health, and systematic review. The co-occurrence network made it possible to observe the relationship between topics and subtopics, such as dental implants with systematic reviews. The diagrams showed the dynamics of the main themes and their different behaviors by subperiods, in which the degree of relevance, development, and associations with other themes varied. Conclusions: It is also possible to note the development of new topics, such as Covid-19, the disappearance of others, such as orthodontics, and the constant presence dental caries topic, which can be considered essential in the research of Brazilian dentistry.
Keywords: Scientific mapping; Author keywords; Co-words analysis; Dentistry research; Co-occurrence network; Scientific maps